Impact of Pre-Dialysis Care on Clinical Outcomes in Peritoneal Dialysis Patients - Spigolon, Dandara N. (2016)
Background: Structured pre-dialysis care is associated with an increase in peritoneal dialysis (PD) utilization, but not with peritonitis risk, technical and patient survival. This study aimed at analyzing the impact of pre-dialysis care on these outcomes. Methods: All incident patients starting PD between 2004 and 2011 in a Brazilian prospective cohort were included in this analysis. Patients were divided into 2 groups: early pre-dialysis care (90 days of follow-up by a nephrology team); and late pre-dialysis care (absent or less than 90 days follow-up). The socio-demographic, clinical and biochemical characteristics between the 2 groups were compared. Risk factors for the time to the first peritonitis episode, technique failure and mortality based on Cox proportional hazards models. Results: Four thousand one hundred seven patients were included. Patients with early pre-dialysis care presented differences in gender (female-47.0 vs. 51.1%, p = 0.01); race (white-63.8 vs. 71.7%, p < 0.01); education (<4 years-61.9 vs. 71.0%, p < 0.01), respectively, compared to late care. Patients with early pre-dialysis care presented a higher prevalence of comorbidities, lower levels of creatinine, phosphorus, and glucose with a significantly better control of hemoglobin and potassium serum levels. There was no impact of pre-dialysis care on peritonitis rates (hazard ratio (HR) 0.88; 95% CI 0.77-1.01) and technique survival (HR 1.12; 95% CI 0.92-1.36). Patient survival (HR 1.20; 95% CI 1.03-1.41) was better in the early pre-dialysis care group. Conclusion: Earlier pre-dialysis care was associated with improved patient survival, but did not influence time to the first peritonitis nor technique survival in this national PD cohort.